Byli i beda - Rodziewiczowna, Maria, 1863-1944. (Warszawa : Wydawn. Alfa, 1991)
An historical novel of the January 1793 insurrection against the Russian Empire.
Originally published: Warszawa : Gebethner i Wolff, 1908.
"Tekst oparto na wydaniu V: Poznan, [1928], Wydawnictwo Polskie" --t.p. verso.
Keywords: Poland -- History -- Partition period, 1763-1796 -- Fiction